Chemical constituents of Amygdalus spp. oil from Iran - Y. Amanzadeh; H. Hajimehdipoor; Z. Abedi; M. Khatamsaz (Iranian Society of Pharmacognosy, 2016)
Background and objectives: Amygdalus with a number of endemic species grow vastly in Iran. Edible sweet almond (A. communis), is cultivated in many countries due to its pharmaceutical, nutritional and cosmetic importance; while almond oil which is rich in oleic acid is known for its economic interest. In the present study, the amount and constituents of oil of six Amygdalus species including A. communis, A. Iranshahrii, A. scoparia, A. lycioides, A. reticulata  and A. elaeagnifolia have been analyzed. Methods: The oil of the plants fruits were obtained with hot and cold methods using n-hexane and their percentages were compared. Then, the oils were analysed by GC after methylation of their constituents. Results: The results demonstrated that the hot method gave higher oil yield than cold method. The amounts of the species oils were almost similar except for A. Iranshahrii which contained the least amount of the oil. The most dominant constituents of the oils comprised of palmitic, stearic, oleic and linoleic acids with almost the same pattern, consisting of mostly oleic acid followed by linoleic and palmitic acids. In all samples only little amounts of stearic acid was detectable. Conclusion: Considering the results of the present study, the evaluated species are of high economic value and could be used as alternatives to sweet almond in pharmaceutical, nutritional and cosmetic industries.